Cost Effects on Multi-Storey Buildings in India - Garg, Dr. P. K.; Agarwal, Richa (Journal of Commerce and Trade, 2018)
The development of multi-storey building construction projects is a complex task which needs not only adequate planning but also requires heavy financial resources. In the big cities, multi-storey building projects are developed as a township where builders have to provide all the necessary amenities to the customers from school to markets, parks, hospitals, community hall, temples, swimming pools, playgrounds etc. Due to these reasons the cost of these projects remains very high. As per the question of cost effects on multi-storey buildings, several factors affect the cost of construction from selection of geographic location to intervention of outside-agencies like government, competitors, suppliers of material and so many others. These factors affect the cost of multi-storey building construction in both sides to a large extent.